Effects of welding parameters on penetration depth in mild steel A-TIG welding - KURTULMUŞ, MEMDUH (SHARIF UNIV TECHNOLOGY, 2018)
A-TIG welding is a welding method in which TIG welding is conducted by covering a thin layer of activating flux on the weld bead beforehand. The most significant benefit of this process is the gain in weld penetration depth. A-TIG welds were produced on mild steel plates with TiO2 flux. The emphasis of this paper was laid upon introducing the effects of various process parameters, namely welding current, welding speed, powder/acetone ratio of the flux, arc length, and electrode angle on mild steel A-TIG welding. The weld penetration depth was measured metallographically. An optimum value was determined for each welding parameter. (C) 2019 Sharif University of Technology. All rights reserved.
Keywords: A-TIG welding parameters; Mild steel A-TIG welding; A-TIG flux; A-TIG flux solvent; A-TIG flux compositions; FLUX